Analysis of The Influence of Financial Target, Rationalization, Dualism Position and Collusion on Fraudelent Financial Statements With The Audit Committee as A Moderation Variable in Sharia Commercial Banks in 2014-2023 - Maharani, Fitria; Kurniawan, Heri (UIN Mataram, 2024)
This research aims to find out the influence of financial targets, rationalization, dualism position and collussion on fraudulent financial statements with audit committees as a moderating variable in Islamic commercial banks in Indonesia. In the research that has been carried out, the method used is quantitative by processing panel data obtained from the annual reports of each Islamic commercial bank. After carrying out the test, the results were obtained that the financial target variable had a positive but not significant effect (had no effect) on fraudulently lent financial statements. rationalization has a positive but not significant effect (has no effect) on fraudulent financial statements. dualism position has a negative and insignificant effect (has no effect) on fraudulently lent financial statements. Collusion has a positive but insignificant effect (has no effect) on fraudulent financial statements. The audit committee cannot moderate the influence of the financial target on fraudulently lent financial statements. The audit committee cannot moderate the influence of rationalization on fraudulent financial statements. The audit committee can moderate the influence of dualism position on fraudelient financial statements and the audit committee cannot moderate the influence of collussion on fraudelent financial statements. In conclusion, financial targets, rationalization, dualism position, and collussion have no effect on fraudulently elegant financial statements. The audit committee is only able to moderate the influence of the dualism position on fraudulent financial statements.